High prevalence of diabetes and other comorbidities in hospitalized patients with COVID-19 in Delhi, India, and their association with outcomes. Issue 1 (January 2021) - Mithal, Ambrish; Jevalikar, Ganesh; Sharma, Rutuja; Singh, Anshu; Farooqui, Khalid J.; Mahendru, Shama; Krishnamurthy, Aishwarya; Dewan, Arun; Budhiraja, Sandeep
Abstract: Background and aims: To study the prevalence and impact of diabetes mellitus and other comorbidities among hospitalized patients with COVID-19. Methods: In a prospective, observational study including consecutive adults hospitalized with COVID-19, clinical outcomes and inflammatory markers were compared in those with and without diabetes. Participants were classified as having mild or severe COVID-19 disease using the WHO ordinal scale. Results: 401 patients (125 females) with median age of 54 years (range 19–92) were evaluated. Of them 189 (47.1%) had pre-existing diabetes and21 (5.2%) had new-onset hyperglycaemia. Overall, 344 (85.8%) and 57 (14.2%) cases had mild and severe COVID-19 disease respectively. The group with diabetes had a higher proportion of severe cases (20.1% vs 9%, p-0.002), mortality (6.3 vs 1.4%, p-0.015), ICU admission (24.3 vs 12.3%, p-0.002), and oxygen requirement (53.4 vs 28.3%, p < 0.001). Baseline Hba1c (n = 331) correlated significantly with outcome severity scores (r 0.136, p-0.013) and 12/15 (80%) of those who succumbed had diabetes. Hypertension, coronary artery disease, and chronic kidney disease were present in 164 (40.9%), 35 (8.7%) and 12 (2.99%) patients respectively. Hypertension was associated with a higher proportion of severe cases, mortality, ICU admission and oxygen administration. Conclusions: We report a high prevalence of diabetes in a hospitalized COVID-19 population. Patients with diabetes or hypertension had more severe disease and greater mortality. Highlights: Diabetes was present in 189/401(47.1%) hospitalized COVID-19 patients and was associated with severe disease and mortality. New onset hyperglycemia was seen 21/401(5.2%) patients and was associated with the worst prognosis. Hypertension was the commonest comorbidity in people with diabetes and was a likely contributor to poor outcomes.